Influence of postoperative complications following esophagectomy for cancer on quality of life: A European multicenter study. Issue 1 (January 2023) - Schuring, N.; Jezerskyte, E.; van Berge Henegouwen, M.I.; Sprangers, M.A.G.; Lagergren, P.; Johar, A.; Markar, S.R.; Gisbertz, S.S.; Markar, Sheraz R.; Zaninotto, Giovanni; Castoro, Carlo; et al.
Abstract: Introduction: Postoperative complications following major surgery have been shown to be associated with reduced health-related quality of life (HRQL), and severe complications may have profound negative effects. This study aimed to examine whether long-term HRQL differs with the occurrence and severity of complications in a European multicenter prospective dataset of patients following esophagectomy for cancer. Methods: Disease-free patients following esophagectomy for cancer between 2010 and 2016 from the LASER study were included. Patients completed the LASER, EORTC QLQ-C30 and EORTC QLQ-OG25 questionnaires >1 year following treatment. Long-term HRQL was compared between patients with and without postoperative complications, subgroup analysis was performed for severity of complications (no, minor [Clavien-Dindo I-II], severe [Clavien-Dindo ≥ III]), using univariable and multivariable regression. Results: 645 patients were included: 283 patients with no, 207 with minor and 155 with severe complications. Significantly more dyspnea (QLQ-C30) was reported by patients with compared to patients without complications ( d i f f e r e n c e i n m e a n s 6.3) . In subgroup analysis, patients with severe complications reported more dyspnea ( difference in means 8.3 ) than patients with no complications. None of the differences were clinically relevant ( difference in means  ≥ 10 points). LASER-based low mood ( OR2.3 ) was statistically different for minor versus severe complications. Conclusion: Comparable HRQL was found in patients with and without postoperative complications following esophagectomy for cancer, after a mean follow-up of 4.4 years. Furthermore, patients with different levels of severity of complications had comparable HRQL. The level of HRQL in esophageal cancer patients are more likely explained by the impact of the complex procedure of the esophagectomy itself.